Assessment of SOX2 performance as a marker for circulating cancer stem-like cells (CCSCs) identification in advanced breast cancer patients using CytoTrack system - Szostakowska-Rodzoś Małgorzata; Fabisiewicz Anna; Myśliwy Izabella; Jagiełło-Gruszfeld Agnieszka; Konieczna Aleksandra; Grzybowska Ewa A. (Open Medicine)
Recent studies have highlighted that one of the main drivers for metastatic formation and resistance to the therapy are circulating tumor cells (CTCs) and cancer stem-like cells (CSCs). Measuring the CTCs has emerged as a non-invasive procedure for selecting the patients with higher risk of progression/relapse. However, still there are no methods enabling the identification of stem-like phenotype of the CTCs.